eIF3a Regulation of NHEJ Repair Protein Synthesis and Cellular Response to Ionizing Radiation - Tumia, Rima; Wang, Chao J.; Dong, Tianhan; Ma, Shijie; Beebe, Jenny; Chen, Juan; Dong, Zizheng; Liu, Jing-Yuan; Zhang, Jian-Ting (Frontiers in Cell and Developmental Biology, 2020)
Translation initiation in protein synthesis regulated by eukaryotic translation initiation factors (eIFs) is a crucial step in controlling gene expression. eIF3a has been shown to regulate protein synthesis and cellular response to treatments by anticancer agents including cisplatin by regulating nucleotide excision repair. In this study, we tested the hypothesis that eIF3a regulates synthesis of proteins important for repair of double strand DNA breaks induced by ionizing radiation (IR). We found that eIF3a up-regulation sensitized cellular response to IR while its down-regulation caused resistance to IR. eIF3a increases IR-induced DNA damages and decreases Non-Homologous End Joining (NHEJ) activity by suppressing synthesis of NHEJ repair proteins. Furthermore, analysis of existing patient database shows that eIF3a expression associates with better overall survival of breast, gastric, lung, and ovarian cancer patients. These findings together suggest that eIF3a plays an important role in cellular response to DNA-damaging treatments by regulating synthesis of DNA repair proteins and, thus, eIIF3a likely contributes to the outcome of cancer patients treated with DNA-damaging strategies including ionizing radiation.